Analisis Sentimen Masyarakat Terhadap Kinerja Persatuan Sepakbola Seluruh Indonesia Menggunakan Metode Backpropagation - Ripki Puja Ika Putra; Muhamad Akbar; Rahayu Amalia (Journal of Information Technology Ampera, 2020)
Sentiment analysis in a sentence describes the part of the consideration of an entity or a event regarding the product, service, topic, issue, person, organization, or event that becomes the target object in sentiment sentences. Judging from several reasons for positive and negative sentiments originating from social media, researchers will use social media not only to communicate between friends, but will be used as a means to find out an aspiration for the community, especially the Indonesian community regarding legal issues or problems related to government. One of the aspirations that will be analyzed is the performance of PSSI. In analyzing this, researchers using the Backpropagation Method are learning methods to reduce error rates by adjusting their weight based on the desired output and target differences. Backpropagation is also a systematic method for multilayer training in Artificial Neural Networks. Backpopagation is said to be a multilayer training method because Backpropagation has three layers in the training process, namely input layer, hidden layer and output layer